Etiology of Kidney Diseases With Proteinuria in the Gambia/West Africa - Vester, Udo; Fombah, Augustin; Hölscher, Maite; Garba, Danlami; Tapgun, Mary; N‘Jai, Pamela Collier; Mendy, Philipp; Bass, Gibril; Muhammad, Abdul K.; Anderson, Suzanne T.; Sanneh, Abdoulie; Onyeama, Charles; et al. (Frontiers in Pediatrics, 2022)
In West Africa, kidney diseases are frequently seen, but diagnostic and therapeutic options are poor due to limited access to specialized facilities. To unravel the etiology and develop clinical guidelines, we collected clinical data and results of kidney biopsy in 121 pediatric and adolescent patients with edema and proteinuria in The Gambia. Workup included clinical examination, urine and serum analysis, and kidney biopsy. Selected cases were treated with steroids. Results: The median age was 14.9 years (range 1.8 – 52.0) at presentation. The most frequent underlying histologies were post-infectious glomerulonephritis (PIGN) in 38%, focal-segmental glomerulosclerosis (FSGS) in 30%, minimal change nephrotic syndrome (MCNS) in 15%, and membranous glomerulonephritis (MGN) in 10% of cases. Patients with PIGN were significantly younger and had less proteinuria and higher serum albumin levels than the other three. Infected scabies was seen more often in cases with PIGN. Clinical parameters could not distinguish patients with FSGS, MCNS, and MGN. Steroid response was prompt in patients with MCNS (remission in 10/10 cases) compared to FSGS (4/19) and MGN (0/4). In summary, the clinical histopathological correlation allow a better approach to therapy and can be the basis for urgently needed interventional studies in steroid-resistant cases.